REALIZATION OF NETWORK NEUTRALITY IN THE INFORMATION SOCIETY CODE IN USER - INTERNET SERVICE PROVIDER RELATION. - Hilpinen, Kimmo (fi=Turun yliopisto|en=University of Turku|, 2016)
Rather unconventionally, the pedigree of grids that are spread on indefinite areas are have a public nature due to their valuation of common benefit. The benefit is qualified according to its nature, such as transmission of voice, electricity etc. In 2014, Finland enacted an Information Society Code, which later in the beginning of the year 2015 was turned into positive law (certain parts 1.7.2015). Through several twists in the law drafting process and rounds in the certain committees, the proposition model was accepted. Given that the holographic reality of the network communications, never mind the technical surroundings, causes restlessness among all relevant sectors during the legislative process, it will do certainly do so afterwards as well. Information Society Code is a monolith, that prescribes the norms to the electronic communications, from the general availability to the practical usage. The preamble of the Code explains that the purpose of the legislation is to secure the efficient and interference-free use of radio frequencies, to foster competition, and to ensure that communications networks and services are technologically advanced, of high quality, reliable, safe, and affordable. Furthermore, the complete Code includes confidentially and the data privacy as well. Hence, the nature of the amendment is certainly a complete, conjunctive motion for the need of a modern networked society, where these issues are best gathered under joint tome. Regardless of the compassionate welcoming, the Code is unproven in several fronts, such as network neutrality. The fundaments of the Code retain the consumer base approach, but allows the operators' freedoms that could hypothetically introduce a different kind of pecking order in the fenced environment of the internet infrastructure in the future. Finland registered a head start with the promulgation of this umbrella act alongside with Netherlands, as similar projects are yet to be implemented in most of the countries, including the ones in European Union. Legislative proceedings will certainly take place throughout the Union as new regulation in telecom sector will be implemented in pursuing the digital single market agenda. Some parts of the Finnish Information Society Code will be amended in the process.